Staphylococcus aureus Adaptation to the Skin in Health and Persistent/Recurrent Infections - Gehrke, Ana-katharina Elsa (2023)
Staphylococcus aureus is a microorganism with an incredible capability to adapt to different niches within the human body. Approximately between 20 and 30% of the population is permanently but asymptomatically colonized with S. aureus in the nose, and another 30% may carry S. aureus intermittently. It has been established that nasal colonization is a risk factor for infection in other body sites, including mild to severe skin and soft tissue infections. The skin has distinct features that make it a hostile niche for many bacteria, therefore acting as a strong barrier against invading microorganisms. Healthy skin is desiccated; it has a low pH at the surface; the upper layer is constantly shed to remove attached bacteria; and several host antimicrobial peptides are produced. However, S. aureus is able to overcome these defenses and colonize this microenvironment. Moreover, this bacterium can very efficiently adapt to the stressors present in the skin under pathological conditions, as it occurs in patients with atopic dermatitis or suffering chronic wounds associated with diabetes. The focus of this manuscript is to revise the current knowledge concerning how S. aureus adapts to such diverse skin conditions causing persistent and recurrent infections.